Libraries in the Manuscript Age - Déroche, François (2023)
Ancient, medieval and modern libraries in various regions (the Muslim world, East Asia, Byzantium, Western Europe) are known only by the manuscripts they kept or documents that shed light on their history. Through case studies the present volume offers an original reflection on the nature of the libraries of the past, their owners' interests, and their role in the intellectual history of the manuscript age.